Communication Culture as a Matrix for Graduate's "Soft Skills" Development - N. G. Chevtaeva; A. S. Nikitina; A. V. Vishnevskaya (Moscow Polytechnic University, 2020)
The article examines the problem of broadcasting the communication culture from the system of education toward the labour market. The authors argue that communication model "teacher - student" acts as a matrix for communication model "employee - employer". In this regard, such a resource as behavioral features of interaction, the communication culture between teacher and student requires special attention. The authors substantiate the thesis that "teacher - student" behavioral model is being reproduced by graduate in the relationship "employee - employer" and reflects "teacher-centric" communication model in the educational process.The authors have carried out a content analysis of the websites of employers in business structures and government organizations. The results confirm a clearly expressed demand for the communication skills of an employee. At the same time, an expert survey of recruiting specialists who assessed the level of communication skills of graduates majoring in economics and management showed a vivid disparity between free use of digital technologies (digital skills) and poor communication skills (soft skills).An analysis of the online questionnaire survey of teachers and students in the field of economics and management of nine Russian universities revealed barriers to the formation of "soft skills" of future graduates: inability to see the interests of the "Other", the habit of pointing fingers instead of solving problems, the lack of client-oriented skills as well as willingness to take personal responsibility for the results of work. The authors outline the ways of restructuring the patterns of teacher and student behavior, which require them to adopt an educational paradigm based on a model of equal interaction of all participants (stakeholders) of educational process. This model will foster the development and mastering of "soft skills" of the future graduates.